1995
DOI: 10.1093/intimm/7.8.1265
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of class-regulation of CD4+ T lymphocyte populations

Abstract: The differential class-regulation of CD4+ T lymphocyte populations is believed to play a major role in determining the qualitative behaviour of the immune system, and in the fate of immune responses in particular. In this article we propose a model for the dynamics of the Th1 and Th2 subpopulations. We put forward the concept of an 'antigenic niche' which allows us to postulate that the key feature underlying the regulation of Th differentiation pathways is the population dynamics of the lymphocytes themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Other authors have also modelled the response of the T helper system to pathogens (Fishman and Perelson, 1994;Carneiro et al, 1995;Muraille et al, 1995;Fishman and Perelson, 1999;Behn et al, 2000). To our knowledge, there is no detailed study on implications of the regulatory mechanisms within the T helper system on the decision-making process.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have also modelled the response of the T helper system to pathogens (Fishman and Perelson, 1994;Carneiro et al, 1995;Muraille et al, 1995;Fishman and Perelson, 1999;Behn et al, 2000). To our knowledge, there is no detailed study on implications of the regulatory mechanisms within the T helper system on the decision-making process.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…They found that T helper responses are polarized towards one phenotype, Th1 or Th2,-owing to autocatalytic Th1/Th2 cross-suppressive processes, similar to our findings-and towards one receptor specificity due to competition for re-stimulation of different clones. Carneiro et al (1995) found that the key feature underlying the regulation of Th differentiation pathways is the population dynamics of the lymphocytes themselves. According to their model the regulation of T helper differentiation is not driven by an APC-dominated selection process-where certain types of antigen are preferentially taken up and presented by particular types of APCs, which activate a certain type of lymphocyte subset.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…They "nd that the cells' average sensitivities on Th1-and Th2-derived cytokines have an important role in the decision-making process. Carneiro et al (1995) also address Th1/2 di!erentiation without direct treatment of antigen clearance and focus the early, decision making aspect of a T helper response. They use the concept of an invariant proliferative driving capacity or antigenic &&niche'' that is indi!erent to the Th1/2 composition of the proliferating lymphocyte pool.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors. (Morel et al, 1992;Fishman & Perelson, 1993Carneiro et al, 1995;Muraille et al, 1995;Lev Bar-or & Segel, 1998) have modelled the Th1}Th2 system, with a variety of approaches and areas of emphasis. We return to comparisons of these models and the one presented here in the discussion.…”
Section: T Helper Cells Canmentioning
confidence: 99%
“…Several other models of basic immunological phenomena have been reported including models of Th1/Th2 crossregulation (82,83), the development of germinal centers (84) and B cell homeostasis (85).…”
Section: Other Immunological Modelsmentioning
confidence: 99%